2014
DOI: 10.1096/fj.14-253732
|View full text |Cite
|
Sign up to set email alerts
|

CD137‐inducing factors from T cells and macrophages accelerate the destabilization of atherosclerotic plaques in hyperlipidemic mice

Abstract: CD137 (4-1BB), a member of the tumor necrosis factor receptor superfamily, has been reported to be expressed in atherosclerotic plaques, and to promote lesion formation. However, the role of CD137 in mediating atherosclerotic plaque stability and the possible underlying molecular and cellular mechanisms are poorly understood. Here, apolipoprotein E-deficient (ApoE(-/-)) and CD137-deficient ApoE(-/-) (ApoE(-/-)CD137(-/-)) mice fed a chow diet for 66 wk were used. CD137 induces plaque instability, which is chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 50 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…163, 164 Advanced atherosclerotic lesions accumulated more macrophages and T cells when 4-1BB was lacking. 165 Lesions in these mice showed signs of vulnerability, accompanied by reduced SMC survival and collagen production. 165 Interestingly, macrophage glucose metabolism is regulated by the interaction of 4-1BBL with its receptor, leading to increased metabolic activity and cell proliferation.…”
Section: Co-stimulatory Pathways In Atherosclerosismentioning
confidence: 97%
See 1 more Smart Citation
“…163, 164 Advanced atherosclerotic lesions accumulated more macrophages and T cells when 4-1BB was lacking. 165 Lesions in these mice showed signs of vulnerability, accompanied by reduced SMC survival and collagen production. 165 Interestingly, macrophage glucose metabolism is regulated by the interaction of 4-1BBL with its receptor, leading to increased metabolic activity and cell proliferation.…”
Section: Co-stimulatory Pathways In Atherosclerosismentioning
confidence: 97%
“…165 Lesions in these mice showed signs of vulnerability, accompanied by reduced SMC survival and collagen production. 165 Interestingly, macrophage glucose metabolism is regulated by the interaction of 4-1BBL with its receptor, leading to increased metabolic activity and cell proliferation. 166 Thus, intervention in 4-1BB-4-BBL interactions might display a valuable therapeutic option in macrophage-driven diseases such as atherosclerosis.…”
Section: Co-stimulatory Pathways In Atherosclerosismentioning
confidence: 97%
“…Circulating CD137L + CD14 + MC was increased in patients with acute ischemic atherosclerotic stroke [74]. CD137 −/− ApoE −/− mice have lower MC and MØ in the aorta [80]. Anti-CD137 monoclonal antibody induced iNOS-positive MØ differentiation in hepatoma tissue in mice [81].…”
Section: Two-way Stimulatory Immune Checkpoint Induces Tissue and Sysmentioning
confidence: 99%
“…These results indicated that CD137 signaling may contribute to the destabilization of atherosclerotic plaques. Recently, our group determined the CD137-mediated molecular mechanisms whereby activation of CD137 signaling decreases the stability of advanced atherosclerotic plaques via its combined effects on T eff cells, VSMCs, and macrophages 87). Briefly, CD137 increases the infiltration of T eff cells into plaque lesion sites, resulting in increased IFN-γ expression.…”
Section: Advanced Vulnerable Plaquementioning
confidence: 99%